Kinetic Studies of the Adsorption of Thorium Ions onto Rice Husk from Aqueous Media: Linear and Nonlinear Approach - Zafar, S.; Khalid, N.; Daud, M.; Mirza, M. L. (The Nucleus, 2015)
The present works deals with the investigation of sorption kinetic of thorium ions onto rice husk employing batch method and radiotracer technique. The study was conducted in nitric acid media at ambient temperature. Maximum adsorption of 24.08 mg Lâˆ’1 of thorium ion was observed at the optimized equilibrium time of 15 minutes, 0.1 g of adsorbent and nitric acid concentration of 1.0 Ã— 10âˆ’4 mol Lâˆ’1 . A comparison was made of the widely used pseudo first and second order kinetic models employing the method of least squares, for the adsorption of thorium ions onto rice husk. Different linear equations for first and second order kinetic were used for this purpose. The results showed the regression value â€œR2 â€ of 0.9711 for one linear equation of pseudo first order and 0.9997, 0.8877, 0.9315 and 0.9315, of type I, II, III, and IV models of linear equations for pseudo second order respectively. Kinetic parameters computed from linear and nonlinear forms of different models are reported and discussed. Among the linear expressions, Type I of the pseudo second order was found to be the most appropriate rate expression for the adsorption of thorium ions on rice husk.